2018
DOI: 10.1002/ldr.2913
|View full text |Cite
|
Sign up to set email alerts
|

The effects of organic and mineral fertilizers on carbon sequestration, soil properties, and crop yields from a long‐term field experiment under a Swiss conventional farming system

Abstract: The effects of mineral fertilizers and organic amendments on soil properties, carbon (C) sequestration, and crop yields are studied in a 37‐year field experiment, Phosphorus–Potassium‐balanced design, in Switzerland. Treatments included a control (mineral fertilization) without nitrogen (N) fertilizers (Min‐N0) and with optimal N (Min‐Nopt) and 5 organic amendments (green manure [Gm], cereal straw [Str], fresh cattle manure in 2 doses 35 and 70 t ha−1 [Ma35 and Ma70] and cattle slurry [Slu]) all receiving the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
68
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(92 citation statements)
references
References 58 publications
10
68
2
2
Order By: Relevance
“…We believe that the principal factor explaining this pattern is organic fertilization, which is regarded as a traditional method for improving soil porosity and enhancing water–air transmission (Conacher & Conacher, ; Loaiza Puerta et al., ). A 37‐year field experiment on the effects of soil properties in Switzerland also showed that organic management supplied a 25 to 80% greater C input to the soil than did mineral fertilization and resulted in better physical properties (Maltas et al., ). Thus, organic fertilization might provide more effective C to counteract the negative effects of frequent vegetable cultivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that the principal factor explaining this pattern is organic fertilization, which is regarded as a traditional method for improving soil porosity and enhancing water–air transmission (Conacher & Conacher, ; Loaiza Puerta et al., ). A 37‐year field experiment on the effects of soil properties in Switzerland also showed that organic management supplied a 25 to 80% greater C input to the soil than did mineral fertilization and resulted in better physical properties (Maltas et al., ). Thus, organic fertilization might provide more effective C to counteract the negative effects of frequent vegetable cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…Organic fertilization has been widely applied in response to the demand for sustainable development (Schrama, de Haan, Kroonen, Verstegen, & Van der Putten, ) and is regarded as a common and traditional method of mitigating soil compaction and improving soil pore characteristics. Maltas, Kebli, Oberholzer, Weisskopf, and Sinaj () examined soil pore characteristics in a 37‐year field experiment in Switzerland using organic and mineral fertilizers and found that organic management produced slightly better soil pore properties than mineral fertilization, and the pore size distribution was also altered. Similar results were obtained by Papadopoulos, Bird, Whitmore, and Mooney () with X‐ray computed tomography (CT) scanning in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of organic amendments such as green manures, farmyard and poultry manures, compost, food‐processing wastes, and biochar have been applied to soils for enhancing soil quality (Bhaduri et al, ; Liu et al, ; Xu, Zhang, Shao, & Sun, ; Yang, Bian, Tang, Zhou, & Li, ). Among these, green manure is a promising way with long‐term effects and low cost (Bai et al, ; Bai, Xu, et al, ; Bai, Yan, et al, ; Bai, Zou, et al, ; Li et al, ; Maltas, Kebli, Oberholzer, Weisskopf, & Sinaj, ; Meier et al, ; Xu et al, ; Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…have shown that the C loss reduction can be much less then the C input through manure (10 to 30 % of C inputs; Leifeld et al, 2009;Oberholzer et al, 2014;Maltas et al, 2018), which likely also applies to compost. Including ley in the crop rotation could also be considered to compensate C losses.…”
mentioning
confidence: 99%
“…Including ley in the crop rotation could also be considered to compensate C losses. According to Maltas et al (2018) green manure or cereal straw application can also be effective measures to prevent or reduce soil degradation, while solid manure has, however, the highest C loss reduction efficiency (compost was not included in the study). The combination of direct eddy covariance measurements and management records provided a unique dataset to study the longterm C budget of the crop field over thirteen years.…”
mentioning
confidence: 99%